Climate change scenarios and sea level rise estimates for California 2008 Climate Change Scenarios Assessment - Cayan, Daniel R. (2009)
Cayan, D., Tyree, M., Dettinger, M., Hidalgo, H., Das, T., Maurer, E., Bromirski, P., Graham, N., and Flick, R., 2009, Climate change scenarios and sea level rise estimates for California 2009 Climate Change Scenarios Assessment: California Energy Commission Report CEC-500-2009-014-D, 50 p. (on-line report in pdf format, 1851 KB)